Analisis Kinerja Komposit Hibrid Aerated Autoclaved Concrete Panel – Lapisan Beton Bertulang Terhadap Lentur - Nuryana Ferryana, Irwan; Sumargo, Sumargo; Oesman, Mardiana (Institut Teknologi Bandung, 2024)
Abstract Aerated Autoclaved Concrete (AAC) precast panels are designed for 400kg/m2 loads. Installation of AAC panels is usually added an additional layer on the top surface as protection. The reinforced concrete layer on top of the AAC panels is often defined as super dead load. However theoretically, the additional layer can increase the strength and stiffness of the panels, provided that both layers work in a monolithic composite. Thus, the layer also functions as a structural component. However, it needs research to convince it. The study is used a fullscale experimental method using 1970x600x125mm AAC panels. The variables are the thickness of the concrete layer and the method of installing shear connectors. Variations of the thickness layers are 30,40, and 50mm with a compressive strength 24.5MPa. The concrete layer is reinforced by D6mm wiremesh 150mm spacing. Shear connectors are made of D6mm deformed rebar, 200mm spacing with two variations: welded and unwelded. Panels are loaded with flexural loads monotonically, using the third-point loading method. The results of the flexural test show that due to the reinforced concrete layer on the ACC panel, the load at the first crack and ultimate increased around 28-89%, and 33-109% respectively, and stiffness 174.70% until 363.31%.